2021
DOI: 10.1111/jocd.14057
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and efficacy of vitamin D supplementation in acne patients: A systematic review and meta‐analysis

Abstract: Acne is a chronically inflammatory disease of the skin. 1 Acne is the second most prevalent skin condition after dermatitis and affects about 85% of teenagers and young adults. 2,3 Acne lesions develop in the pilosebaceous units that primarily distribute on the check, chin, forehead, and back. 4 The pathogenesis of acne covers four aspects: hyper seborrhea, altered keratinization of the pilosebaceous duct, Propionibacterium acnes (P. acnes), and inflammation.Previous research studies have confirmed that inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…A meta-analysis showed an interesting inverse correlation between patients' vitamin D levels and clinical severity of their acne. Vitamin D treatment of sebocytes in vitro showed anti-inflammatory properties with reduced expression of interleukin-6 and matrix-metalloproteinase 9 which might explain a possible pathomechanism [65,66]. Yee et al showed that oral zinc supplementation in acne patients led to a reduced appearance of inflammatory eruptions as compared with a cohort without zinc, concluding that zinc may constitute a safe and cost-effective addition to pharmacotherapy [67,68].…”
Section: Vitamins and Trace Elementsmentioning
confidence: 99%
“…A meta-analysis showed an interesting inverse correlation between patients' vitamin D levels and clinical severity of their acne. Vitamin D treatment of sebocytes in vitro showed anti-inflammatory properties with reduced expression of interleukin-6 and matrix-metalloproteinase 9 which might explain a possible pathomechanism [65,66]. Yee et al showed that oral zinc supplementation in acne patients led to a reduced appearance of inflammatory eruptions as compared with a cohort without zinc, concluding that zinc may constitute a safe and cost-effective addition to pharmacotherapy [67,68].…”
Section: Vitamins and Trace Elementsmentioning
confidence: 99%
“…It is the most common skin condition after dermatitis and has an estimated global prevalence of 9.38%. [ 20 21 ] Acne patients have not only local tissue damage but also increased oxidative stress burden. [ 8 ] Recent studies have shown that oxidative stress has an important role in acne initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, according to a meta-analysis, vitamin D supplementation affected sputum conversion and was therefore recommended for consideration during TB therapy 21 . In contrast, another meta-analysis confirmed no relationship between vitamin D supplementation and sputum conversion 22 .…”
Section: Introductionmentioning
confidence: 89%